1991
DOI: 10.1111/j.1745-9125.1991.tb01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and Punishment: An Empirical Assessment*

Abstract: Evidence for a relationship between unemployment and imprisonment has been regarded as "elusive" and "conflicting. " Such conclusions have been based primarily on aggregate-level data. Individual-level data have provided only indirect evidence for this relationshb. This research considers prosecution, incarceration, and length of incarceration outcomes for I , 970 criminal defendants arrested in 1982. Multivariate logit and OLS estimates show a signifcant, strong, and independent impact of unemployment on pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
5

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 37 publications
4
83
1
5
Order By: Relevance
“…Our primary dependent variable, prison term, is an offender's expected minimum sentence, which helps account for the non-uniform nature of parole eligibility for South Carolina offenses (Freiberger and Hilinski, 2013; see also Chiricos and Bales, 1991;Spohn and Cederblom, 1991). 7 8 Because the data include extreme outliers such as life and death sentences, we top coded 0.44% of the cases at a maximum of 720 months, or an expected minimum sentence of 60 years in prison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our primary dependent variable, prison term, is an offender's expected minimum sentence, which helps account for the non-uniform nature of parole eligibility for South Carolina offenses (Freiberger and Hilinski, 2013; see also Chiricos and Bales, 1991;Spohn and Cederblom, 1991). 7 8 Because the data include extreme outliers such as life and death sentences, we top coded 0.44% of the cases at a maximum of 720 months, or an expected minimum sentence of 60 years in prison.…”
Section: Methodsmentioning
confidence: 99%
“…Using the expected minimum rather than the imposed maximum accounted for these differences in parole eligibility (Chiricos and Bales, 1991;Gertz and Price, 1985;Spohn and Cederblom, 1991). The expected minimum was calculated by adjusting the imposed maximum sentence by a parole eligibility multiplier as determined by the controlling offense (e.g., 0.25, 0.33, 0.85, 1.0) and rounded up to the nearest month (less than 200 of the 17,671 original sentences are nonintegers).…”
Section: Methodsmentioning
confidence: 99%
“…According to Akers (1996, p. 127), "Self-report studies find class and race variations in criminal and delinquent behavior, but they are not as great as class and race differences in officially arrested, convicted, and/or imprisoned populations ." Thus, when unemployed citizens are disproportionately found in incarcerated populations (Chiricos, 1991), it is not likely due to their increased involvement with criminal behavior. Nor can the overrepresentation of African Americans in the criminal justice system be explained by their higher involvement in criminal behavior.…”
Section: Media Activitymentioning
confidence: 99%
“…Offenders who spend time in jail before trial are more likely to spend time in incarceration after trial (Chiricos & Bales 1991). Demuth (2003:876) suggested that, "pretrial detention is punishment before conviction."…”
Section: Disparities In Pretrial Releasementioning
confidence: 99%